2012
DOI: 10.1007/s10452-012-9417-9
|View full text |Cite
|
Sign up to set email alerts
|

Succession in the aquatic Sarracenia purpurea community: deterministic or driven by contingency?

Abstract: The development of a community through time, or succession, is generally described as the orderly replacement of species until a deterministic, stable endpoint is reached. However, stochastic factors, coupled with intrinsic biotic factors, such as herbivory or predation, can cause communities within the same habitat to become highly dissimilar in composition. Much research on the succession of terrestrial systems has been conducted, but factors influencing the succession of a terrestrial system may not apply t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
1
19
1
Order By: Relevance
“…Alternatively, the filter occurs later in community development for bacteria and interactions with the higher trophic level as well as resource input and extrinsic factors may shape the bacterial community in some aspects through time. Within the NY study site, this pattern is supported by findings in Gray [32], in which communities converge to be more similar in bacterial composition at the end of the season and to contain a different composition when compared to communities at the beginning of the season.…”
Section: Discussionsupporting
confidence: 64%
“…Alternatively, the filter occurs later in community development for bacteria and interactions with the higher trophic level as well as resource input and extrinsic factors may shape the bacterial community in some aspects through time. Within the NY study site, this pattern is supported by findings in Gray [32], in which communities converge to be more similar in bacterial composition at the end of the season and to contain a different composition when compared to communities at the beginning of the season.…”
Section: Discussionsupporting
confidence: 64%
“…The aquatic communities that were collected from the 4-week-old leaves were designated as "late-succession communities" and the aquatic communities that were from 2-week-old leaves were designated as "early-succession communities". A 1-month duration is a reasonable interval for this community to reach late-succession because the community consists of bacteria and protists, which have fast generation times (Gray 2012). Note that early-and late-succession communities from Québec already experienced W. smithii predation at the time of sampling [W. smithii lay their eggs immediately after pitcher opening (Smith 1902)].…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial density was then standardized across sites by adjusting the volume of the communities with autoclaved deionized water, resulting in 1.09 × 10 7 bacteria per ml for each origin. This technique is standard for research conducted on the Sarracenia system, as it has been shown that the members of the food web are able to easily survive and maintain normal interactions, even when placed directly into deionized water (Kneitel and Miller , Hoekman , Gray , Kadowaki et al , Kneitel , Zander et al ). As a control, an equal volume of water from each of the five sites was also pooled to make the ‘mixed origin’ community.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was conducted over 6 d, which is equivalent to approximately 18 to 24 generations of protozoans (Lüftenegger et al ) and 48 generations of bacteria (Gray et al ). The experiment ended when the bacteria and protozoans were expected to reach their carrying capacities in this system (Gray , Kadowaki et al ). The fast generation time of microbial systems thus allows experiments to be conducted over a short amount of time, while producing results equivalent to longer‐term experiments on larger organisms (Srivastava et al ).…”
Section: Methodsmentioning
confidence: 99%